2016
DOI: 10.1080/19476337.2016.1247298
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of interactions between coffee and cardamom, their type, and strength in relation to interactions in a model system

Abstract: This paper presents a study on determination of antiradical potential, ferric-reducing antioxidant power (FRAP), chelating power (CHEL), OH• scavenging capacity (OH), superoxide dismutase-like activity, lipoxygenase (LOXi), and xanthine oxidase (XOi) inhibitory potential and also interactions between the phytochemicals from coffee and cardamom based on their bioaccessibility in vitro. Evaluation of interactions between coffee and cardamom in a model system showed that phenolic compounds may be responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…This trend was maintained along the in vitro digestion process, with very few exceptions (Figure 4a and Figure 4b) that occurred particularly in the gastric phase (time 120 min in both varieties and time 60 min in the variety 'Latina'). The highest potency of the inhibition of lipoxygenase activity after digestion was also previously reported for coffee, ginger and cardamom extracts (Durak et al, 2015(Durak et al, , 2017.…”
Section: Antioxidant and Anti-inflammatory Activitiessupporting
confidence: 71%
“…This trend was maintained along the in vitro digestion process, with very few exceptions (Figure 4a and Figure 4b) that occurred particularly in the gastric phase (time 120 min in both varieties and time 60 min in the variety 'Latina'). The highest potency of the inhibition of lipoxygenase activity after digestion was also previously reported for coffee, ginger and cardamom extracts (Durak et al, 2015(Durak et al, , 2017.…”
Section: Antioxidant and Anti-inflammatory Activitiessupporting
confidence: 71%
“…Studies [ 7 ] showed the synergistic action of ferulic and chlorogenic acids as LOX inhibitors. The same kind of interaction was found between chlorogenic and cinnamic acid [ 25 ], as well as chlorogenic and vanillic acid [ 26 ]. So far there is no information on TPO activators and their interactions in the literature.…”
Section: Resultsmentioning
confidence: 59%
“…There are some studies showing the influence of phytochemical compounds on the activity of other enzymes, e.g., lipoxygenase. Studies conducted by Durak et al [39] demonstrated inhibitory activity of pure and dietary polyphenols on LOX activity and interactions among these inhibitors. The biological advantages of polyphenols included in plant sources of food appear useful for the development of bioactive functional food.…”
Section: Resultsmentioning
confidence: 99%